Introgression of trypanotolerance genes. - Koudande, O.D. (Wageningen University & Research, 2000)
This doctoral dissertation consists of 6 chapters: general introduction; Estimating recombination in an advanced intercross population of mice (paper submitted for publication); A model for population growth of laboratory animals subjected to marker-assisted introgression: how many animals do we need? (published in Heredity (1999) 82, 16-24); Strategies to optimize marker-assisted introgression of multiple unlinked QTL (quantitative trait loci) (published in Mammalian Genome (2000) 11, 145-150); Trypanotolerance QTL introgression in mice: experimental results; general discussion. It was shown how the size of a breeding experiment increases with the number and size of the QTL region to introgress. Biological factors to be considered when estimating the required size of an introgression experiment are also highlighted. The experiment in mice showed that QTL introgression is feasible and successful, and that the background genotype is an important factor to be considered when analysing the results of such an experiment. The general discussion focuses on the introgression of trypanotolerance genes in cattle with an emphasis on Sub-Saharan zones in Africa.